China’s COVID-19 Governance Through the Lens of Biopolitics - Alika Wara Dewanti (Jurnal Hubungan Internasional, 2026)
As we move into modernisation and globalisation, the world is exposed to different diseases that could be deadly and dangerous for our citizens. The COVID-19 pandemic, which originated in China, exemplifies a disease that was recognized as a global health crisis due to its rapid worldwide spread. To combat this pandemic, China developed multiple strategies, including an intensive combination and application of health policy and surveillance, all of which can be analysed using the thinking of the French philosopher Michel Foucault. This study examines how China’s pandemic strategy can be explored through Foucault’s concepts of biopolitics and panopticism. This framework explains how modern governance puts the population at the centre of the political agenda, supported by a surveillance system to ensure compliance. Although biopolitics and panopticism are evident in China’s Zero-COVID policy, which was integrated with the country’s Social Credit System (SCS), the author found that Foucault alone cannot fully account for China’s strategies, as they do not fully align with the country’s political and cultural context. Therefore, this study highlights the usefulness and limitations of applying Foucault’s analytical framework to an authoritarian government such as China. Keywords: China, Michel Foucault, COVID-19, Biopolitics, Panopticism.